Урахування сучасних євроінтеграційних тенденцій скандинавських країн для вітчизняного освітнього простору - Орос Ільдіко; Orosz Ildikó; Oros Ildiko; Біда Олена; Bida Olena; Гуттерер Єва; Hutterer Éva (Видавництво «Код», 2024)
Резюме. У статті показано, що система освіти скандинавських країн будується переважно за однією моделлю. Основним принципом, закладеним у систему освіти в скандинавських країнах, є доступність навчання незалежно від соціального походження, етнічної чи національної належності, релігійних переконань чи обмежених фізичних можливостей. Поширення міграційних процесів зробило скандинавські країни мультикультурними, тому інтегроване навчання забезпечує реалізацію права кожного члена суспільства на рівний доступ до навчання, опанування професії й визначення свого місця в суспільстві. Головною метою вищої освіти скандинавських країн наразі є зближення академічної і професійної вищої освіти. З’ясовано характерні риси освітньої політики Норвегії. Проаналізовано Данську систему освіти, яка має деякі відмінності від освітніх систем інших скандинавських країн.

Abstract. The article shows that the educational system of the Scandinavian countries is built mainly according to one model. The main principle embedded in the education system in the Scandinavian countries is the availability of education regardless of social origin, ethnic or national affiliation, religious beliefs or limited physical capabilities. The spread of migration processes has made the Scandinavian countries multicultural, so integrated education ensures the realization of the right of every member of society to equal access to education, mastering a profession and determining their place in society. The main goal of higher education in the Scandinavian countries is currently the convergence of academic and professional higher education. Characteristic features of the education policy of Norway are clarified and the leading trends of higher education in Norway are shown. Peculiarities of Norwegian higher education: public administration, dominance in the innovation process of the higher education system, a small share of foreign funding sources. The Danish education system, which has some differences from the educational systems of other Scandinavian countries, is analyzed. Education for life is declared the basis of the educational process in Denmark. Finland as an educational space is built on the principle of providing all citizens with equal opportunities for education, regardless of socio-cultural and physiological characteristics. Common to all Scandinavian countries are the basic principles of the functioning of the education system: equality of access to educational services, the state nature of funding, the focus of the content of education on the formation of soft skills, effective communication skills, civic and socio-cultural values. A characteristic feature of the educational space of the Scandinavian countries is the popularization of lifelong learning.
Taking into account the current european integration trends of the scandinavian countries for the domestic educational space
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00014095 https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-8
Keywords: скандинавські країни; Норвегія; Данія; Фінляндія; система освіти; навчання впродовж життя